PERBEDAAN PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA YANG MEMPEROLEH MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY-TWO STRAY (TS-TS) DAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DI KELAS VII SMP ISLAM AL-FALAH JAMBI - Putri Mulyani; Zulyadaini Zulyadaini; Eni Defitriani (Universitas Batanghari Jambi, 2019)
This research was motivated by the low mathematical problem-solving ability of the seventh grade students of Al-Falah Islamic Junior High School Jambi. This research is a quasi-experimental study with Nonequivalent Pretest-Posttest Control Group Design design and a pattern that is all students of Al-Falah Islamic Middle School in the academic year 2017/2018. Sampling used purposive sampling, which is a sample consisting of three classes namely class VII.1, VII.2 and VII.4 where the given sample is different. The instruments used in this study are teaching materials and mathematical solution ability tests. The research data were analyzed using non parametric Kruskal Wallis H. statistical results. The results showed that there were differences faced by students who studied with two types of Two Stay-Two Stray (TS-TS), Problem Based Learning (PBL) learning models, and models conventional learning. After further using the Games-Howell test, the differences in the TS-TS class and PBL class then become PBL classes and Conventional classes.Keywords: Mathematical problem solving ability, Two stay-Two Stray (TS-TS), Problem Based Learning (PBL).